2014
DOI: 10.1038/jcbfm.2014.136
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Reveals the Focal Area of Spreading Depolarizations and a Variety of Hemodynamic Responses in a Rat Microembolic Stroke Model

Abstract: Spreading depolarizations (SDs) occur in stroke, but the spatial association between SDs and the corresponding hemodynamic changes is incompletely understood. We applied multimodal imaging to visualize the focal area of selected SDs, and hemodynamic responses with SDs propagating over the ischemic cortex. The intracarotid infusion of polyethylene microspheres (d ¼ 45 to 53 mm) produced multifocal ischemia in anesthetized rats (n ¼ 7). Synchronous image sequences captured through a cranial window above the fron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 38 publications
5
63
0
Order By: Relevance
“…Also, different propagation patterns of SD are observed in OIS. Bere et al using OIS in multi-focal stroke model in rats found that some SD waves gradually got extinguished and some SD waves might avoid the cortical region with lowest perfusion within the field of view during the propagation [34]. Santos et al detected diverse expansion patterns of SD with OIS in the cortex of swine: spiral wave, reverberating wave, and collision of two waves ( Figure 5) [16].…”
Section: Spatial-temporal Patterns Of Sd In Oismentioning
confidence: 99%
See 1 more Smart Citation
“…Also, different propagation patterns of SD are observed in OIS. Bere et al using OIS in multi-focal stroke model in rats found that some SD waves gradually got extinguished and some SD waves might avoid the cortical region with lowest perfusion within the field of view during the propagation [34]. Santos et al detected diverse expansion patterns of SD with OIS in the cortex of swine: spiral wave, reverberating wave, and collision of two waves ( Figure 5) [16].…”
Section: Spatial-temporal Patterns Of Sd In Oismentioning
confidence: 99%
“…However, in pathological states, such as reduced perfusion pressure and ischemia, SD may trigger spreading ischemia and are owing to changes in light scattering, blood volume, and hemoglobin and cytochrome oxidation state. OIS is particularly appropriate for studying SD, because 1) a large-scale cerebral cortex can be studied simultaneously and numerous timepoints can be got over time as SD waves propagate; 2) OIS is able to provide information about propagating patterns of SD [16]; 3) OIS in multi-wavelength studies can correlate perfusion-related changes to electrophysiological changes of SD [17]; 4) it is important to identify the optical profile of SD, since OIS studies involving seizure, electrical stimulation, or mechanical perturbation of the cortex can inadvertently induce SD. In the past few years, OIS has been used to study SD in normal and pathological conditions [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the longer duration of SD in the ischemic brain is attributed to the collective, lower rate of depolarization and repolarization, rather than the prolongation of complete depolarization itself 65 . 67 .…”
Section: The Recovery Of Resting Membrane Potential After Depolarizatmentioning
confidence: 75%
“…Ischemia shifts this balance toward the domination of the initial vasoconstrictive (hypoemic) element of the pattern, possibly as a function of decreasing perfusion pressure 28,65 . Matching this concept, we have identified 6 types of CBF kinetics ranging from dominating hyperemia to prolonged cortical spreading ischemia with intermediate forms.…”
Section: The Hyperemic Response To Spreading Depolarization Diminishementioning
confidence: 99%
“…At present, the deficiency of the SD-associated CBF response is accepted to mediate neurodegeneration, because the insufficient CBF response sustains the state of depolarization and delays repolarization by depriving the tissue at risk of essential nutrients required to maintain ionic balance across neuronal cell membranes [14,32]. Baseline CBF (100%) is given as a horizontal line [34].…”
Section: 2patophysiological Impact Of Spreading Depolarizationmentioning
confidence: 99%